4D printed zero Poisson's ratio metamaterial with switching function of mechanical and vibration isolation performance. (November 2020) - Liu, Kai; Han, Le; Hu, Wenxia; Ji, Longtao; Zhu, Shengxin; Wan, Zhishuai; Yang, Xudong; Wei, Yuling; Dai, Zongjie; Zhao, Zeang; Li, Zhen; Wang, Pengfei; et al.
Abstract: The unusual properties of mechanical metamaterials are determined by the configuration of artificial periodic structures. However, the mechanical performance of conventional metamaterials is irreversible and cannot perceive and respond to the changes in the environment. In present study, a zero Poisson's ratio metamaterial with intelligent switching mechanical properties and vibration isolation effect is proposed. Based on a 4D printing method of shape memory polymer, this metamaterial is created that can sense temperature changes and switch mechanical properties. The macroscopic deformation and the morphology change of the metamaterial during compression tests are analyzed using experimental and finite element methods. The irregular buckling distortion of the metamaterial is eliminated by cylindrical design, and controllable and adjustable local deformation and stress-strain curve are achieved based on microstructure gradient design. Subsequently, this work focused on the vibration isolation performance of metamaterials, and found fascinating shock absorption performance. Compared with traditional linear spring, this metamaterial spring can effectively reduce the vibration amplitude of certain frequency bands before reaching the resonance peak, which provides a new realization method for low-frequency vibration isolation design. Graphical abstract: Unlabelled Image Highlights: A 4D printed zero-Poisson's ratio metamaterial with programmable shapes, thermally tunable mechanical performance is created. A cylindrical design is proposed to eliminate buckling distortion in unit cells during compression, . Based on gradient design, controllable and defect-insensitive local deformation can be achieved in the metamaterial. The metamaterial can effectively reduce the vibration amplitude of certain frequency bands before the resonance peak.